Glycoengineering of Darbepoetin-α in CHO-DG44 Cells through Overexpression of α-2,3-sialyl-transferase and CMP-sialic Acid Transporter - Adi Santoso; Endah Puji Septisetyani; Ratna Dwi Ramadani; Yana Rubiyana; Pekik Wiji Prasetyaningrum; Popi Hadi Wisnuwardhani; Arizah Kusumawati; Neny Nuraini (HAYATI Journal of Biosciences, 2022)
Sialic acid plays a very important role in determining the circulation life span of glycoprotein in various organisms. Therefore, having a high content of sialic acid is needed by glycoprotein therapeutic agents to be able to function as desired. For example, Darbepoetin (DPO), the 5 N-linked erythropoietin showed higher bioavailability and efficacy compared to 3 N-linked erythropoietin. However, in the DPO production process, the molecular weight can vary and is highly dependent on the content of sialic acid and its production host. To improve the DPO sialic acid contents in our CHO-DG44 expressing DPO, we have engineered the cells through overexpression of α-2,3-sialyl-transferase (ST) and CMP-sialic acid transporter (CST). The DPO contained in the supernatant of the engineered cells was analyzed by Western blot and characterized by using PNGase-F or neuraminidase enzyme digestions. The results showed that, two clones, overexpressing ST or CST, were obtained. The clones showed higher molecular weight of DPO as compared to DPO expressed by the parental cells, yet retained the same protein backbone. The overexpression of these two genes does not affect cell growth. This suggests that may be these cells beneficial for therapeutic glycoproteins.